Impact of climate change on mental health and well-being - Samanta, Debabrata 1987-; Garg, Muskan (Advances in psychology, mental health, and behavioral studies (APMHBS) book series, 2024)
Climate change has far-reaching consequences beyond its environmental impact. It also significantly affects human social and mental well-being, both at individual and community levels. Addressing the social and mental well-being impacts of climate change requires a multi-faceted approach that includes both mitigation and adaptation strategies. This involves reducing greenhouse gas emissions, supporting sustainable development, building climate-resilient communities, enhancing social support systems, and investing in mental health services to address the specific challenges of climate change. In this groundbreaking exploration, Impact of Climate Change on Mental Health and Well-Being transcends the traditional discourse on climate change by delving into its repercussions on the social and mental fabric of our communities. From the foundational examination of the connections between climate change, social stability, food security, and mental health to the nuanced exploration of eco-anxiety, ethical dilemmas, economic instability, and climate-induced migration, this work leaves no stone unturned in its quest for knowledge. The book not only identifies the problems but also offers solutions. By emphasizing a multi-faceted approach, it advocates for reducing greenhouse gas emissions, sustainable development, climate-resilient communities, and robust mental health services. It empowers readers--academics, professionals, policymakers, and the general informed public--to take actionable steps toward a sustainable and mentally resilient future. The interdisciplinary nature of this work makes it a valuable resource for graduate and postgraduate students, professionals in various fields, educators, and policymakers.